SE-DEA-based Approach to Determining the Hub Growth Potential of Airports. Issue 7 (April 2020) - Wang, Yu; Li, Bowen; Wang, Qian; Che, Tong
Abstract: Determining which airports can grow to hubs in a transportation system is a basis of hub-and-spoke network design. From the perspective of airport operation efficiency, this paper presented a SE-DEA (super-efficiency data envelopment analysis)-based approach to identify those airports that possess the hub growth potential. Firstly, the urban population, urban GDP, and the number of navigation points were considered as input variables. The throughput, the proportion of transit passengers, the proportion of international passengers, the normal rate of airport release and the proportion of base airline were treated as output variables. An empirical analysis with the data of several main American airports in 2018 was solved by DEA-SOLVER Pro 5.0 software. The results show us: (1) the top three airports are LAS (McCarran International Airport), ATL (Hartsfield-Jackson Atlanta International Airport) and MIA (Miami International Airport), (2) the results are consistent with the reality and this proposed method could lay theoretical basis on finding airports which have the potential to become hub ones.